Brain Lesion Load and Anatomic Distribution in Patients With Juvenile Clinically Isolated Syndrome Predicts Rapidly Advanced to Multiple Sclerosis. (September 2018) - Menascu, Shay; Legarda, Carolina; Miron, Shmuel; Achiron, Anat
The aim was to assess brain lesion load and anatomical distribution in patients with juvenile clinically isolated syndrome and define magnetic resonance imaging (MRI) variables associated with rapidly advancing to multiple sclerosis. Patients were followed for one year after disease onset. Patients who experienced a second relapse were defined as those who rapidly advanced to multiple sclerosis. In all, 46 juvenile patients with a clinical presentation suggestive of multiple sclerosis were evaluated; 21 with gadolinium-enhancing lesions on initial brain MRI were excluded as they had already fulfilled the diagnosis criteria for multiple sclerosis. A total of 25 patients, 10 males and 15 females (mean ± SE age at onset 15.6 ± 0.6 years), met the definition of clinically isolated syndrome. The presence of a corpus callosum lesion at onset significantly differentiated between sustained clinically isolated syndrome and patients who rapidly advanced to multiple sclerosis.